Problems and directions of strengthening liability for customs offences in the context of modern challenges and trends in customs legislation - Hrechaniuk , Roksolana; Hrechaniuk , Serhii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article examines the current issues of strengthening liability for customs offences in the context of modern challenges of globalisation, integration processes and dynamic changes in customs legislation. It is noted that the efficiency of the customs system directly depends on the proper legal regulation of liability for violation of customs rules, which contributes to the economic security of the State. The author identifies the main disadvantages of the current system of bringing to liability for customs offences, in particular, insufficient coordination between governmental authorities, gaps in the legal framework and low level of legal awareness among foreign economic operators.The author proposes strategic directions for improving liability for customs offences, including updating the legislative framework in line with European standards, introducing digital technologies for monitoring customs procedures, and strengthening international cooperation in the field of combating smuggling and other customs offences. Particular attention is paid to the need to improve the skills of customs authorities, as well as to the formation of a culture of legal responsibility through educational and information campaigns.The results of the study may be useful for scholars, legislators and practitioners dealing with customs regulation, as well as for improving the national customs policy of Ukraine in the context of integration into the European legal area.